Enhanced cisplatin chemotherapy sensitivity by self-assembled nanoparticles with Olaparib - Zhang, Tao; Li, Xiao; Wu, Liang; Su, Yue; Yang, Jiapei; Zhu, Xinyuan; Li, Guolin (Frontiers in Bioengineering and Biotechnology, 2024)
Cisplatin (CDDP) is widely used as one kind of chemotherapy drugs in cancer treatment. It functions by interacting with DNA, leading to the DNA damage and subsequent cellular apoptosis. However, the presence of intracellular PARP1 diminishes the anticancer efficacy of CDDP by repairing DNA strands. Olaparib (OLA), a PARP inhibitor, enhances the accumulation of DNA damage by inhibiting its repair. Therefore, the combination of these two drugs enhances the sensitivity of CDDP chemotherapy, leading to improved therapeutic outcomes. Nevertheless, both drugs suffer from poor water solubility and limited tumor targeting capabilities. To address this challenge, we proposed the self-assembly of two drugs, CDDP and OLA, through hydrogen bonding to form stable and uniform nanoparticles. Self-assembled nanoparticles efficiently target tumor cells and selectively release CDDP and OLA within the acidic tumor microenvironment, capitalizing on their respective mechanisms of action for improved anticancer therapy. In vitro studies demonstrated that the CDDP-OLA NPs are significantly more effective than CDDP/OLA mixture and CDDP at penetrating cancer cells and suppressing their growth. In vivo studies revealed that the nanoparticles specifically accumulated at the tumor site and enhanced the therapeutic efficacy without obvious adverse effects. This approach holds great potential for enhancing the drugs' water solubility, tumor targeting, bioavailability, and synergistic anticancer effects while minimizing its toxic side effects.